Aplikasi Penginderaan Jauh Citra Landsat-8 Untuk Pembuatan Peta Batimetri Di Perairan Pantai Jumpai, Klungkung, Bali - Ida Ayu Made Inten Melinia; I Dewa Nyoman Nurweda; I Gusti Ngurah Putra Dirgayusa (Journal of Marine Research and Technology, 2023)
Klungkung Regency is the smallest regency in the province of Bali, Indonesia. The waters of Jumpai Beach are one of the areas in Klungkung, which is one area that is used by the surrounding population for fishing activities for fishermen to obtain fishery products. Remote sensing technology has been applied because of its effectiveness and the significance of its use in compiling and revising resource maps. It is also helpful to support resource planning and management. A bathymetry map is a map that describes the depth of the sea and is presented using contour lines. Contour lines are abstract lines connecting several locations or areas with the same height or depth. Remote sensing techniques are available to determine the ocean’s depth because the air has signals from the very bottom of the ocean with strong solid wavelengths. However, the penetration of electromagnetic energy is limited. Therefore, remote sensing techniques are adopted to infer water depth and shallowness. One of the satellites that can be used for bathymetry mapping is Landsat-8. Landsat imagery has a spatial resolution of 30 meters, complemented by the visible channels required to extract bathymetric maps. Accurate estimation of shallow water area bathymetry for the safety of small boat navigation such as fishing and for benthic studies. Remote sensing technology can be considered one of the most desirable alternative tools for bathymetry development.